Risk factors for methotrexate treatment failure in tubal ectopic pregnancy: a retrospective cohort study - Linru Fu; Xinyan Liu; Zhao Tian; Zhe Du; Xinyi Wang; Xiuqi Wang; Xiaodong Li; Tao Xu; Zhijing Sun (BMC Pregnancy and Childbirth)
Abstract Background Ectopic pregnancy (EP) accounts for approximately 2% of all pregnancies, with tubal ectopic pregnancies (TEPs) being the most common type. Methotrexate (MTX) is a noninvasive and effective medical management option for TEP, but failure rates range from 10 to 36%, posing challenges in clinical practice. Identifying risk factors for MTX treatment failure is crucial to improve patient outcomes and guide clinical decision-making. This study aimed to determine the risk factors associated with MTX failure in TEP patients and support personalized treatment strategies. Methods This retrospective study included female patients who were diagnosed with TEP at Peking Union Medical College Hospital (PUMCH) between January 2016 and December 2022. Patients received MTX treatment initially, with dosing intervals and protocols varying according to clinical practice. MTX treatment failure was defined as the need for surgery after MTX administration. The study included two groups: patients who failed MTX treatment (n = 91) and those who succeeded in treatment (n = 268). Univariate and multivariate logistic regression analyses were performed to identify significant predictors of MTX treatment failure. A nomogram was developed to visualize the predictive factors. Results A total of 359 patients were included, with 268 (74.7%) succeeding with MTX and 91 (25.3%) required surgery. Specifically, 282 patients (78.6%) received 1-dose MTX, whereas 77 (21.4%) received 2-dose MTX. Univariate analysis revealed that gravidity, previous EP, gestational age, pretreatment β-human chorionic gonadotropin (β-hCG) level, number of MTX treatments, and presence of a visible yolk sac in ultrasound were significant predictors (all P < 0.05). Multivariate analysis confirmed that higher gravidity (odds ratio (OR) = 1.2487, 95% confidence interval (CI): 1.0103 – 1.5433, P = 0.040) and elevated pretreatment β-hCG levels (OR = 1.0006, 95% CI: 1.0004 – 1.0008, P < 0.001) were independent risk factors. Number of MTX treatments was a significant protective factor (OR = 0.4409, 95% CI: 0.2153 – 0.9025, P = 0.025). The nomogram incorporating these six risk factors was developed. Conclusion Higher gravidity and elevated β-hCG levels were significant predictors of MTX failure, while more MTX doses provided a protective effect. These findings underscore the importance of personalized MTX treatment strategies to improve outcomes in TEP. However, the limitations of this study, including its retrospective and single-center design, suggest that further prospective multicenter studies are needed to validate these results. Trial registration The trial is registered at http://www.chictr.org.cn . [registration number: ChiCTR2400081314; registration date: 2024–02-28 (prospectively registered)].